RELEVANSI UU No. 7 TAHUN 2011 TENTANG MATA UANG DENGAN FENOMENA MUNCULNYA MATA UANG VIRTUAL, STUDI KASUS FENOMENA BITCOIN DI INDONESIA - Sigit Somadiyono (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
The development of the virtual world has penetrated the world of national borders. Not only unlimited distances but applicable laws in cyberspace are increasingly not bound by the laws of the state. In buying and selling in cyberspace, especially the internet, money that is used is no longer monotone in currency issued by a particular country but has created a payment system that does not require legitimacy of a country. The most phenomenal emergence of Bitcoin is that its use as currency in a purchase transaction has been appointed exceeds a country's currency. Several countries in the world have determined stance against the imposition of BitCoin, some accept and some refuse. Indonesia has not determined a clear stance for the development of new Bitcoin in Indonesia limited to the internet world and not stray into the real world.Keyword: Relevance, Law no. 7 In 2011, the Virtual Currency, Phenomenon, BitCoin, Indonesia